2012
DOI: 10.1128/aem.06646-11
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Stress Resistance Patterns among stx Genotypes and Genetic Lineages of Shiga Toxin-Producing Escherichia coli O157

Abstract: ABSTRACTTo evaluate the relationship between bacterial genotypes and stress resistance patterns, we exposed 57 strains of Shiga toxin-producingEscherichia coli(STEC) O157 to acid, freeze-thaw, heat, osmotic, oxidative, and starvation stresses. Inactivation rates were calculated in each assay and subjected to univariate and multivariate analyses, including principal component analysis (PCA) and cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…This result suggests a relatively narrow phylogenetic lineage for the 026 strains included in this study. Low variability in heat resistance between closely related E. coli 0157:H7 strains has been reported previously (31). These results indicate that the selection of E. coli strains in pressure and heat resistance studies cannot be extrapolated from the serotypes or phylogenetic groups.…”
Section: Discussionmentioning
confidence: 59%
“…This result suggests a relatively narrow phylogenetic lineage for the 026 strains included in this study. Low variability in heat resistance between closely related E. coli 0157:H7 strains has been reported previously (31). These results indicate that the selection of E. coli strains in pressure and heat resistance studies cannot be extrapolated from the serotypes or phylogenetic groups.…”
Section: Discussionmentioning
confidence: 59%
“…The human isolates, predominantly LSPA-6 lineage I or I/II, typically carried stx2a alone or in combination with stx1 or stx2c while LSPA-6 lineage II cattle isolates carried stx2c alone or in combination with stx1 [38]. These investigators also demonstrated that lineage I ( stx1 - stx2 ) isolates showed multiple stress resistances when compared to the lineage II ( stx1 - stx2c ) genotypes [39].…”
Section: Discussionmentioning
confidence: 94%
“…Lineages defined by LSAP-6 were used to demonstrate differences in pathogenicity among different lineage strains (Dowd and Williams, 2008). However, there are some discrepancies in the interpretation of LSPA-6 codes in terms of lineages in previous descriptions (Franz et al, 2012;Lee et al, 2012;Sharma et al, 2009;Whitworth et al, 2010;Yokoyama et al, 2011b). Manning et al (2008) proposed the clade phylogenetic groups as defined by SNP analysis.…”
Section: Introductionmentioning
confidence: 99%